2021
DOI: 10.1093/mnras/stab1794
|View full text |Cite
|
Sign up to set email alerts
|

The connection between star formation and supermassive black hole activity in the local Universe

Abstract: We present a study of the active galactic nucleus (AGN) activity in the local Universe (z < 0.33) and its correlation with the host galaxy properties, derived from an Sloan Digital Sky Survey (SDSS DR8) sample with spectroscopic star-formation rate (SFR) and stellar mass ($\mathcal {M}_{\ast }$) determination. To quantify the level of AGN activity we used X-ray information from the XMM-Newton Serendipitous Source Catalogue (3XMM DR8). Applying multiwavelength AGN selection criteria (optical BPT-diagrams… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 121 publications
0
17
1
Order By: Relevance
“…Previous studies, using either the specific black hole accretion rate parameter (λ s,BHAR , Georgakakis et al 2017;Aird et al 2018Aird et al , 2019Torbaniuk et al 2021, see also next section) or the specific X-ray luminosity (Yang et al 2018), found that the stellar mass of the host galaxy, may affect how the AGN and galaxy properties are linked. Mountrichas et al (2021c) found indications that the increase of SFR norm at L X,2−10keV > 2 − 3 × 10 44 erg s −1 is more evident for AGN that live in galaxies that have stellar masses within a specific range (log [M * (M )] ∼ 11−11.5) while the most massive ones do not present this feature in their SFR norm −L X relation.…”
Section: Sfr Of X-ray Agn Relative To Star Forming Galaxies As a Func...mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies, using either the specific black hole accretion rate parameter (λ s,BHAR , Georgakakis et al 2017;Aird et al 2018Aird et al , 2019Torbaniuk et al 2021, see also next section) or the specific X-ray luminosity (Yang et al 2018), found that the stellar mass of the host galaxy, may affect how the AGN and galaxy properties are linked. Mountrichas et al (2021c) found indications that the increase of SFR norm at L X,2−10keV > 2 − 3 × 10 44 erg s −1 is more evident for AGN that live in galaxies that have stellar masses within a specific range (log [M * (M )] ∼ 11−11.5) while the most massive ones do not present this feature in their SFR norm −L X relation.…”
Section: Sfr Of X-ray Agn Relative To Star Forming Galaxies As a Func...mentioning
confidence: 99%
“…The estimated parameter is the SFR norm , defined as the ratio of the SFR of AGN to the SFR of MS galaxies. Results from studies that followed this approach (e.g., Mullaney et al 2015;Masoura et al 2018;Bernhard et al 2019;Masoura et al 2021;Torbaniuk et al 2021), though, may suffer from systematics. These systematic could be introduced by a number of factors.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies, using either the specific black hole accretion rate parameter (λ s,BHAR , Georgakakis et al 2017;Aird et al 2018Aird et al , 2019Torbaniuk et al 2021, see also following section) or the specific X-ray luminosity (Yang et al 2018), found that the stellar mass of the host galaxy may affect how the AGN and galaxy properties are linked. Mountrichas et al (2021a) found indications that the increase in SFR norm at L X,2−10 keV > 2−3 × 10 44 erg s −1 is more evident for AGN that live in galaxies that have stellar masses within a specific range (log [M * (M )] ∼ 11−11.5) while the most massive ones do not present this feature in their SFR norm −L X relation.…”
Section: Sfr Of X-ray Agn Relative To Star Forming Galaxies As a Func...mentioning
confidence: 99%
“…The estimated parameter is the SFR norm , defined as the ratio of the SFR of AGN to the SFR of MS galaxies. However, results from studies that followed this approach (e.g., Mullaney et al 2015;Masoura et al 2021Masoura et al , 2018Bernhard et al 2019;Torbaniuk et al 2021) may suffer from systematic errors introduced by a number of possible factors. For example, different methods are applied for the estimation of the host galaxy properties (SFR, M * ) of AGN and those of star forming (non-AGN) systems; the definition of MS is not strict; and different selection criteria have been applied to the AGN and non-AGN galaxy samples.…”
Section: Introductionmentioning
confidence: 99%
“…The advantage of X-ray surveys is that they allow us to detect sources obscured in other wavelengths, since X-ray spectra emitted from the nuclei do not strongly interact with surrounding material. Telescopes such as X-ray Multi-Mirror Mission -Newton (XMM-Newton; Jansen et al 2001) have helped to identify a larger number of AGN, including absorbed and low-luminosity AGN, helping to distinguish them from galaxies without an active nucleus (e.g., Caccianiga et al 2007, Elías-Chávez et al 2021, Torbaniuk et al 2021. On the other hand, optical surveys such as the Sloane Digital Sky Survey SDSS (York et al 2000) have provided information about identifications and redshifts over ∼ 30 per cent of the sky.…”
Section: Introductionmentioning
confidence: 99%